TEMPLATE-BASED MODEL FOR SHORT-TERM FORECASTING OF THE NUMBER OF TRANSACTIONS IN RETAIL CLOTHING STORES - Haluza, Oleksii; Kostiuk, Olga; Nikulchenko, Artem; Akhiiezer, Olena; Aslandukov, Mykola (Bulletin of National Technical University "KhPI". Series: System Analysis, Control and Information Technologies, 2022)
Obtaining predictive values of indicators based on historical data represented by time series plays a crucial role in making business decisions in various industries. One of these areas of application is the task of predicting the number of transactions in retail stores in order to optimally plan the working hours of employees and achieve maximum customer satisfaction with the quality of service. The choice of an appropriate time series forecasting model depends on the forecast horizon, as well as the characteristics of the time series, namely trend, seasonality, cyclicality, and irregularity. Traditional time series analysis and forecasting methods are designed to handle a single seasonality in a time series, but in the presence of multiple seasonality, these methods do not work satisfactorily. The use of time series decomposition methods is characterized by computational complexity. The use of machine learning methods is also not always advisable for a number of different reasons. Thus, it is necessary to use simple adaptive models, based on selected patterns, for recurring seasonal data of complex structure. The main goal of this article is to develop a successful adaptive model and propose methods for using it for short-term forecasting of the number of transactions based on time series data. For estimation purposes, a set of hourly time series of the number of customers (transactions) of some retail chain stores, characterized by multiple seasonality, is used. The results of computational experiments show that the proposed template-based model is quite effective for obtaining short-term predictive values. This model, characterized by simplicity, intuitiveness and a minimum number of tuning parameters, can actually be applied to any area of data represented by time series.